Analisis Optimalisasi Pemanfaatan Alumunium dari Sisa Proses Produksi Menjadi Bahan Baku Produksi Dengan Mempertimbangkan Aspek Kualitas, Biaya dan Mutual Benefit Dengan Pihak Ketiga - Kristovel Sihaloho; Koswara Koswara (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract PT ABC is a company engaged in the two-wheeled automotive manufacturing industry that wants to optimize the use of aluminum scrap left over from machining production and processing it into raw materials is carried out by third parties or suppliers with quality standards set by PT ABC. However, processed raw materials are the cause of high product defects because the ferrous content is always high. The first stage in reducing the level of disability is to identify the influencing factors. The method used is a fishbone diagram, followed by the Taguchi method to find out the factors that most influence the cause of product defects. From the results of data processing with a fishbone diagram, there are three influential factors. Among these three factors, the factor with the greatest influence is sought which results in product quality deviating from quality standards. From the results obtained it was concluded that product defects were caused by the percentage of ferrous content of 1.15%, while the percentage of application results using the Taguchi method was 0.09%. Decreasing the percentage of ferrous content affects product quality improvement, lower production raw material purchase costs and mutual benefits with third parties.